2013
DOI: 10.2527/jas.2011-4874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dam parity on litter performance, transfer of passive immunity, and progeny microbial ecology1

Abstract: Litter performance and progeny health status may be decreased in progeny derived from primiparous sows but improve with increasing parity. The objective was to evaluate litter performance, the production and passive transfer of Ig, and fecal microbial populations in progeny derived from first parity (P1) compared with fourth parity (P4) dams. Litter performance was recorded for P1 (n = 19) and P4 (n = 24) dams including number of pigs/litter (total born, born live, stillbirths, mummified fetuses, prewean morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 42 publications
(55 reference statements)
11
63
0
Order By: Relevance
“…These results are consistent with previous findings that no effect was found on piglet growth when these results are compared to sows nursing complete litters (Terry et al, , 2014. Piglets suckling primiparous as opposed to multiparous sows were lighter and grew more slowly during lactation, consistent with previous reports in the literature (Mahan, 1998;Carney-Hinkle et al, 2013). These data demonstrate that the stimulation of a lactation oestrus by way of full physical boar exposure can allow for the weaning age of all piglets to be determined on their requirements, rather than the need to reduce the farrowing to re-mating interval.…”
Section: Discussionsupporting
confidence: 96%
“…These results are consistent with previous findings that no effect was found on piglet growth when these results are compared to sows nursing complete litters (Terry et al, , 2014. Piglets suckling primiparous as opposed to multiparous sows were lighter and grew more slowly during lactation, consistent with previous reports in the literature (Mahan, 1998;Carney-Hinkle et al, 2013). These data demonstrate that the stimulation of a lactation oestrus by way of full physical boar exposure can allow for the weaning age of all piglets to be determined on their requirements, rather than the need to reduce the farrowing to re-mating interval.…”
Section: Discussionsupporting
confidence: 96%
“…() suggested that the development of the ‘mature’ gut microbiota in swine is accelerated by the addition of tylosin, although the gut microbiota of untreated pigs eventually reaches this state as well. Therefore, it may be that once this climax community is attained, the gut microbiota is increasingly more resistant to dietary perturbations, including antibiotics (Carney‐Hinkle et al ., ). In addition, despite using the maximum dosage of tylosin and chlortetracycline allowed in Canada for growth promotion in swine, we did not detect any differences in growth rate between diet groups (Holman & Chenier, ).…”
Section: Discussionmentioning
confidence: 97%
“…Other factors such as dam parity and greater ingestion of creep feed and faecal material by the LWG piglets could also have an influence on gut microbiota. (Carney‐Hinkle et al., ; Mori et al., ; Torrallardona, Andrés‐Elias, López‐Soria, Badiola, & Cerdà‐Cuéllar, ). Some studies reported that eater “creep feed” piglets have lower performance during the lactation and weaning weight (Pluske et al., ; Sulabo et al., ).…”
Section: Discussionmentioning
confidence: 99%